LTE for UMTS : Evolution to LTE-Advanced - Holma, Harri (Harri Kalevi), 1970-; Toskala, Antti (Wiley, 2011)
"Still providing the thorough breakdown of the key areas of LTE of the first edition, this new revised edition of LTE for UMTS includes some important new sections on updates to the standards, as well as a look at possible future developments"--Provided by publisher.